Diversité floristique des peuplements ligneux du Ferlo, Sénégal - Ndiaye Ousmane; Diallo Aly; Sagna Moustapha Bassimbé; Guissé Aliou (VertigO, 2014)
The combined effect of the pejoration climate and anthropogenic pressure caused a progressive degradation of Sahel natural resources. This phenomenon has not spared the woody stratum in these areas which is the main source of fodder in dry season. The rehabilitation of these ecosystems necessarily involves specific ecological knowledge, hence the interest in to make a diagnosis of the floristic diversity of the woody stratum. Dendrometric method was used for this study in Ferlo, in 5 localities along gradients of ecological factors (Widou, Téssékéré Labgar and the east-west axis and Kamb and deali on the north-south axis). This method allowed to make an inventory of 35 species belonging to 27 genres and 19 families. Also the statistical treatments of the data obtained show that flora is dominated by the family of Combretaceae, Mimosaceae and Caesalpiniaceae. Balanites aegyptiaca, Calotropis procera and Boscia senegalensis are the predominant species. Floristic richness is more important in northern Ferlo which has a low similarity with the southern part.